Modeling power system operation with intermittent resources - Marinovici, M. C.; Kirkham, H.; Glass, K. A.; Carlsen, L. C. (2013 IEEE PES Innovative Smart Grid Technologies (ISGT), 2013)
Electricity generating companies and power system operators face the need to minimize total fuel cost and maximize total profit over a given time period. These issues become optimization problems subject to a large number of constraints that must be satisfied simultaneously. The grid updates due to smart-grid technologies, plus the penetration of intermittent resources in electrical grid, introduce additional complexity to the optimization problem. The Renewable Integration Model (RIM) is a computer model of an interconnected power system. It is intended to provide insight and advice on complex power systems management, as well as answers to questions relating to the integration of renewable energy. This paper describes the RIM basic design concept, solution method, and the initial suite of modules that it supports.